Exploring the potentials of educational robotics in the development of computational thinking: a summary of current research and practical proposal for future work - Ioannou, Andri; Makridou, Eria (My University, 2018)
Educational robotics are increasingly appearing in educational settings, being considered a useful supporting tool for the development of cognitive skills, including Computational Thinking (CT), for students of all ages. Meanwhile, there is an overwhelming argument that CT will be a fundamental skill needed for all individuals by the middle of the twenty-first century and thus, should be cultivated in the early school years, as part of the child’s analytical thinking and as a principal component of Science-Technology-Engineering-Mathematics (STEM) education. This study reviews published literature at the intersection of CT and educational robotics, particularly focused on the use of educational robotics for advancing students’ CT skills in K-12. The reviewed articles reveal initial evidence suggesting that educational robotics can foster students’ cognitive and social skills. The paper discusses specific areas for further inquiry by learning researchers and learning practitioners. Such inquiry should start from a widely agreed definition of CT and validated measurement instruments for its assessment. A practical framework for the development of CT via robotics is next in demand, so as instructional designers and educators can implement it consistently and at scale.
Keywords: Computational thinking; Educational robotics; Robotics in education